Padrões espacial e temporal do atropelamento de mamíferos em uma rodovia no cerrado brasileiro - Oliveira, Adriana Nepomuceno de (Universidade Federal de São Carlos, 2011)
This thesis is divided into a general introduction on the issue of roads ecology and the main factors that lead to the general public and the animals roadkills, followed by a chapter that investigates if there is spatial and seasonal patterns of medium and big mammals roadkills in a road (SP-225) in northeast of São Paulo State, Brazil. The road is located in a region of Cerrado, semideciduous forest and riparian vegetation. Data were collected during the years 2006, 2007 until February 2008. 114 roadkills were recorded for medium and large mammals.-vehicle collision were recorded,. The two species most hit were Cerdocyon thous and Lepus europaeus, with 32 and 22 records respectively .It was analyzed if there was spatial clustering of roadkills per kilometer between Km 75-235 and noticed the Km 146- is the one that has the highest number of roadkills, with 7 records, followed by Km 115 and Km 125, with 5 and 4 records respectively. When road is divided into sections of 5 km each, the passages that had higher indices of collision were Km 145-150, followed by passage of Km 125-130, with 15 and 10 roadkills respectively. This analysis showed that the most impacted areas have been the most probable for roadkills. In these sections, it is indicate the application of mitigation measures. The temporal patterns of roadkills distribution were not clear, except in 2006, when the rainy season showed a higher rate of roadkills than dry season. Using three species as a model, it was analyzed the relationship between the landscape around the Road and roadkills frequency. Three species were chosen, the two most frequently hit (Cerdocyon thous and Lepus europaeus) and one threatened (Chrysocyon brachyurus). The roadkills of C. thous were associated to areas of reforestation and less urban, while the roadkills of L. europaeus were in areas of planting (reforestation and orange s crop). The urban areas and with less pasture were associated to the C. brachyurus roadkills.
Keywords: Ecologia; Ecologia de estradas; Colisão animalveículo; Mamífero; Rodovias; Trópicos; Paisagem; Mammals; Road; Animal-vehicle collision; Tropics; Landscape; CIENCIAS BIOLOGICAS::ECOLOGIA